Comparative Evaluation of 2 Work Experience Approaches for Predominantly Black Youth in a Rural Community: Implications for Public Health Workforce Development. Issue 1 (January 2023) - Frerichs, Leah; Smith, Cambray; Hoover, Stephanie; Robinson-Ezekwe, Nicole; Khanna, Anisha; Ellerby, Brian; Joyner, Linda; Wynn, Mysha; Wrenn, Jonina; Stith, Doris; Tessler Lindau, Stacy; Corbie, Giselle
Abstract : Context: In order to create a more diverse workforce, there is a need to involve historically excluded youth in public health–related work. Youth involvement in asset-based work experience approaches is especially relevant for rural areas with workforce shortages. Objective: To explore the public health workforce development implications of community-based career exploration and asset mapping work experience from the perspective of Black youth. Design: We used qualitative in-depth interviews with youth, aged 14 to 22 years, who participated in a work experience program anchored in several rural counties in southeastern United States. A phenomenological lens was applied for qualitative analyses with iterative, team-based data coding. Participants were also surveyed pre- and postprogram to supplement findings. Program: A rural community-based organization's work experience program consisted of 2 tracks: (1) Youth Connect—a career exploration track that included work placement within community agencies; and (2) MAPSCorps—a track that employs youth to conduct asset mapping for their community. Results: We interviewed 28 of 31 total participants in the 2 tracks. We uncovered 4 emergent profiles in how youth described shifts in their perceptions of community: (1) Skill Developers; (2) Community Questioners; (3) Community Observers; and (4) Community Enthusiasts. In comparing between tracks, youth who participated in work experience that involved asset mapping uniquely described increased observation and expanded view of community resources and had greater increases in research self-efficacy than youth who participated only in career exploration. Conclusion: Asset mapping work experience that is directly placed in rural communities can expose Black youth to and engage them in essential public health services (assessing and mobilizing community assets) that impact their community. This type of program, directly integrated into rural communities rather than placed near academic centers, could play a role in creating a more diverse public health workforce.